Pengaruh Moralitas Individu, Pengendalian Internal Dan Asimetri Informasi Terhadap Kecenderungan Kecurangan Akuntansi (Studi Empiris Pada Perangkat Daerah Kota Binjai) - Nadia Zariska; Reza Hanafi Lubis (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
The delay in the completion of the financial statements is that there is inadequate asset management, the distribution of BLT funds is not right on target, and the performance of BUMD is still a lot less healthy, especially in Binjai. The purpose of this study was to examine and analyze the effect of individual morality on the tendency of accounting fraud, internal control on the tendency of accounting fraud, information asymmetry on the tendency of accounting fraud and the influence of individual morality, internal control, and information asymmetry on the tendency of accounting fraud. work that will be carried out during the research, so it is expected to provide an overview and which direction will be carried out in carrying out the research. Accounting fraud is the lower the individual's morality, the higher the tendency of accounting fraud. Differences of opinion between superiors and subordinates will able to influence subordinates in making decisions. implementation or basis for fulfilling several safeguards from internal control. The government of Binjai city including SKPD in its environment must improve internal control, to minimize the potential for accounting fraud, effective internal control is needed, both for supervision.Keywords: Individual Morality, Internal Control, Information Asymmetry, Accounting Fraud Tendency